Diagnosis dan Tatalaksana Kalazion Eksaserbasi Akut ODS - Rahmat, Aprin Nabila; Graharti, Risti; Maulana, Muhammad (CV. Jasa Sukses Abadi, 2024)
Chalazion is a granulomatous inflammation with lipogranuloma or chronic non-infectious inflammation of the eyelid, in the form of a nodule formed due to inflammation and obstruction of the tarsal meibomian gland or zeis. This chalazion often occurs in all age groups, but the chalazion occur more commonly in the productive age. We report the case of a 20-year-old man with complaints of a lump on the upper eyelid, at the left and right eye for 4 months before entering the hospital. The lump is initially small but gets bigger over time, becomes red, feels painful and lumpy. This complaint has been repeated since 10 months ago. Currently the lump no longer feels painful, itchy or hot, but the lump is now permanent. On ophthalmological examination, it was found that the superior eyelid of the right eye had a nodule measuring ±5 mm and the superior eyelid of the left eye had a nodule measuring ±3mm. The diagnosis made was acute exacerbation of chalazion of right eye, then the patient was given non-medicamentosa therapy, medicamentosa, and operative treatment.